2007
DOI: 10.1080/02841850601026393
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of timed barium esophagogram in newly diagnosed idiopathic achalasia: clinical and manometric correlates

Abstract: All patients with newly diagnosed achalasia presented with delayed emptying of barium the esophagus at TBE. The estimated emptied volume of barium (related to the ingested volume) correlated inversely with the basal tone and the relaxation pressure of the LES. Including estimation of the volume of emptied barium at TBE resulted in closer correlation with manometric values of LES tone than using the parameters traditionally recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Review of prior literature regarding correlation of symptoms with TBE or HRM findings shows inconsistent results . Andersson and colleagues reported an inverse correlation between TBE width and postprandial chest pain ( r = −0.44) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Review of prior literature regarding correlation of symptoms with TBE or HRM findings shows inconsistent results . Andersson and colleagues reported an inverse correlation between TBE width and postprandial chest pain ( r = −0.44) .…”
Section: Discussionmentioning
confidence: 99%
“…8,10 TBE, HRM, and symptoms Review of prior literature regarding correlation of symptoms with TBE or HRM findings shows inconsistent results. 3,8,9,[13][14][15][16][17][18][19] Andersson and colleagues reported an inverse correlation between TBE width and postprandial chest pain (r = −0.44). 13 In a study by Yaghoobi and colleagues, active and passive regurgitation showed significant correlation with LES pressure.…”
Section: Principal Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Esophageal emptying was assessed by the height of the barium column at the 1‐minute and 5‐minute time‐points, respectively 10 . The estimated volume of the barium column was also included as a measure of esophageal emptying as it has been shown that this variable correlates with the manometric tone of the LES in patients with idiopathic achalasia 14 . The volume of barium in the esophagus was calculated according to the formula: (mean radius) 2 × 3.14 × height (after correction for magnification by dividing the measurements with a factor of 1.35).…”
Section: Methodsmentioning
confidence: 99%
“…With respect to barium contrast studies, Andersson et al. demonstrated that delayed emptying correlates with increased LES pressures, thereby demonstrating a positive correlation between radiographic and manometric findings in achalasia patients 13 . Furthermore, the authors were able to demonstrate a statistically significant inverse relationship between the duration of symptoms and emptying capacity of the esophagus.…”
Section: Discussionmentioning
confidence: 95%